The Application of 5C Analysis on the Micro People’s Business Credits Financing with Murabaha contract in Sharia Bank of Indonesia Buah Batu 2 Branch Office - Mimin Mintarsih; Nur’aeni Nur’aeni; Azmi Arumsari; Ummi Zulfatu Rohmah (International Journal of Research in Community Services, 2023)
Based on the results of observation and interviews, the background of this research is the fluctuation of the clients’ late-paid installment data due to the bank’s improper in analyzing potential clients. Therefore, the bank applied a 5C analysis method to prevent the clients’ failed and/or late payments at the Sharia Bank of Indonesia (BSI) Buah Batu 2 branch office. This research aims to discover how to apply the 5C principle on micro People’s Business Credits (KUR) financing at the Sharia Bank of Indonesia (BSI) Buah Batu 2 branch office. The descriptive qualitative method is applied to this research with the 5C principle as the object. Furthermore, observation, interviews, literature review, and documentation are the techniques used to collect this research’s primary data.The research findings lead to the conclusion, that is, the application of 5C analysis has been implemented by the bank before they approved the financing. Nevertheless, the bank still gets a problem in observing the character aspect of the clients for the reason that one’s character is way too complex and difficult to observe. Moreover, there are three points for the aspects of character, three points for the aspects of capacity, five points for the capital aspects, six points for the collateral aspects, and lastly, two points for the condition aspects.